Epitope mapping of two immunodominant domains of gp41, the transmembrane protein of human immunodeficiency virus type 1, using ten human monoclonal antibodies. - Xu, J Y (1991)
Immunogenic regions of the gp41 transmembrane protein of human immunodeficiency virus type 1 (HIV-1) were previously mapped by examining polyclonal sera from HIV-infected patients and rodent polyclonal and monoclonal antibodies (MAbs) to peptides of gp41. To define the epitopes within these regions to which infected humans respond during the course of infection, the specificity of human MAbs to these regions had to be studied. Using 10 human MAbs identified initially by their reactivity to whole gp41 in HIV-1 lysates, the epitopes within the immunodominant region of gp41 and within a second immunogenic region of gp41 have been mapped. Thus, five MAbs (from five different patients) to the immunodominant domain of gp41 in the vicinity of the cysteines at positions 598 and 604 (hereinafter designated cluster I) reacted with a stretch of 11 amino acids from positions 590 to 600. Four of these five MAbs were reactive with linear epitopes, while one MAb required the conformation conferred by the disulfide bridge between the aforementioned cysteines. Three MAbs to cluster I revealed dissociation constants ranging from 10(-6) to 10(-8) M, depending on the MAb tested and the size of the synthetic or recombinant peptide used in the assay. Five additional MAbs reacted with a second immunogenic region between positions 644 and 663 (designated cluster II). Four of these five MAbs were specific for conformational determinants. Titration of sera from HIV-infected patients showed that there was about 100-fold more antibody to cluster I than to cluster II in patients' sera, confirming the immunodominance of cluster I.